2021
DOI: 10.1128/jcm.02052-20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Rapid Emergence of Daptomycin Resistance in Corynebacterium : a Multicenter Study

Abstract: Background: Members of the genus Corynebacterium are increasingly recognized as pathobionts and can be very resistant to antimicrobial agents. Previous studies have demonstrated that Corynebacterium striatum can rapidly develop high-level daptomycin resistance (HLDR) (minimum inhibitory concentration [MIC] ≥256 μg/mL). Here we conducted a multi-center study to assay for this in vitro phenotype in diverse Corynebacterium species. Methods: Corynebacterium clinical isolates (n=157) from four medical centers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Initially, daptomycin resistance had been only reported in the genus of corynebacteria in C. jeikeium [ 6 ]; later isolates of daptomycin-resistant C. striatum were found [ 19 , 40 , 49 , 50 , 51 , 52 ]. Moreover, a recent study showed that several corynebacteria species could rapidly develop daptomycin non-susceptibility, including HLDR (high-level daptomycin resistance), after a short daptomycin exposure period [ 53 ].…”
Section: C Striatum Resistomementioning
confidence: 99%
“…Initially, daptomycin resistance had been only reported in the genus of corynebacteria in C. jeikeium [ 6 ]; later isolates of daptomycin-resistant C. striatum were found [ 19 , 40 , 49 , 50 , 51 , 52 ]. Moreover, a recent study showed that several corynebacteria species could rapidly develop daptomycin non-susceptibility, including HLDR (high-level daptomycin resistance), after a short daptomycin exposure period [ 53 ].…”
Section: C Striatum Resistomementioning
confidence: 99%
“…This has been chiefly described with C. striatum, where sequential clinical specimens from few reported cases exhibited emergence of HLDR during daptomycin therapy [ 23 , 25 , 26 ]. It was also demonstrated in vitro, where 90%–100% of C. striatum isolates developed HLDR after daptomycin exposure [ 23 , 27 ]. The emergence of HLDR has also been described in other species, including C. jeikeium and C. amycolatum [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also demonstrated in vitro, where 90%–100% of C. striatum isolates developed HLDR after daptomycin exposure [ 23 , 27 ]. The emergence of HLDR has also been described in other species, including C. jeikeium and C. amycolatum [ 27 ]. After 24 hours of in vitro daptomycin exposure, 12% of 119 non- striatum isolates developed HLDR [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Promising antibiotic alternatives may be represented by tigecycline or daptomycin [ 44 ]. Indeed, C. striatum seems to be susceptible to daptomycin, whether alone or combined with rifampicin [ 37 ]; despite the emergence of high-level daptomycin resistance has been already described [ 18 , 45 ]. In addition, high levels of resistance to a wide range of other antimicrobial drugs, including most β-lactams [ 11 ], macrolides [ 46 ], fluoroquinolones [ 47 ], aminoglycosides [ 48 ], and cotrimoxazole [ 3 ], have been reported.…”
Section: Discussionmentioning
confidence: 99%